1994
DOI: 10.1002/hipo.450040406
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of long‐term potentiation in the hippocampal dentate gyrus of the freely moving rat

Abstract: The ability of the perforant path/dentate granule cell synapse of the hippocampal formation to establish and maintain enhanced levels of synaptic transmission in response to tetanization (long-term potentiation, LTP) was investigated in freely moving rats at 15, 30, and 90 days of age. Measures of 1) the slope of the population excitatory postsynaptic potential (EPSP), and 2) the population spike amplitude (PSA) obtained before, and at several times following tetanization, were used to evaluate the magnitude a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 20 publications
2
15
0
1
Order By: Relevance
“…To test retention of the task, the platform was removed for a 60-s probe test 4 hr after the last trial on day 6. Mice that had been trained with four trials per day spent more time in the platform quadrant than in all others (controls, F (3,28) ϭ 57.17, P Ͻ 0.0001; runners, F (3,28) ϭ 16.70, P Ͻ 0.0001). Mice trained with two trials per day did not show a significant preference for the platform quadrant (controls, F (3,32) ϭ 1.53, P Ͼ 0.23; runners, F (3,32) ϭ 2.56, P Ͻ 0.07), although for runners, the trend appeared stronger (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test retention of the task, the platform was removed for a 60-s probe test 4 hr after the last trial on day 6. Mice that had been trained with four trials per day spent more time in the platform quadrant than in all others (controls, F (3,28) ϭ 57.17, P Ͻ 0.0001; runners, F (3,28) ϭ 16.70, P Ͻ 0.0001). Mice trained with two trials per day did not show a significant preference for the platform quadrant (controls, F (3,32) ϭ 1.53, P Ͼ 0.23; runners, F (3,32) ϭ 2.56, P Ͻ 0.07), although for runners, the trend appeared stronger (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although newborn cells are a small percentage of the total cells in the granule cell layer, it is possible that new neurons affect hippocampal physiology more than do mature cells (27). Indeed, in immature rats, dentate gyrus LTP lasts longer than in adults (28). Newborn cells in the adult brain may be similar to those generated during development.…”
Section: Discussionmentioning
confidence: 99%
“…The slope of the fEPSP is an indicator of the synaptic strength (Bronzino et al, 1994). We did not observe significant changes in the inputoutput relationship between the stimulus intensity and fEPSP slopes in wild-types (n 5 8) relative to mutants (n 5 7; Fig.…”
Section: Basal Synaptic Transmission At Perforant Path-granule Cell (mentioning
confidence: 89%
“…Although the new cells are a small percentage of the granule cell layer, several studies have indicated that they have greater plasticity than do mature cells. Indeed, in immature rats, DG LTP lasts longer than in adults (Bronzino et al 1994 ) . In another study, it was found that putative young cells had a lower threshold for LTP and were unaffected by GABA inhibition, indicating enhanced plasticity in the young cells (Wang et al 2000 ) .…”
Section: Synaptic Plasticitymentioning
confidence: 99%